THE SPECIFICIS OF THE LEARNING ACTIVITY OF THE CHILDREN AGED BETWEEN 6-9 YEARS IN THE CONTEXT OF INTEGRALITY - PASCARI, Valentina (Acta et Commentationes, Sciences of Education, 2019)
The article sets out a vision of the functional development of the body that points the boundaries of the development of the child and goes differently at different age levels in the sense of forming the learning activity. Crossing scientific activity characteristics of learning pedagogy, generate approaches that include as many features applicable to each age period. There are examined the internal and external learning conditions of the learning activity. By analyzing intercorrelations between specific features of learning at children of 6-9 years, we want to show why we should return to this issue, which really is not a new one. It seems that it should be extended, for including dialectical perspective on this age, which we are trying to approach in the first educational node